The Effect Of Dividend Announcements On Stock Price Movements At Pt. Aneka Tambang Persero TBK (ANTM) - Lisa Oktafiani; Yun Fitriano; Kamelia Astuty (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the effect of dividend announcements on stock price movements of PT Aneka Tambang (Persero) Tbk (ANTM). The research adopts a quantitative approach using an event study method to examine the market reaction before and after the dividend announcement. The data used in this study are secondary data in the form of daily closing stock prices and the Indonesia Composite Index (IHSG) during the observation period, which covers 15 days before and 15 days after the dividend announcement. Data analysis was conducted using the paired sample t-test with the help of SPSS Statistics 27 to determine whether there are significant differences in abnormal returns before and after the dividend announcement. The results indicate that the dividend announcement of PT Aneka Tambang (Persero) Tbk in 2023 and 2024 did not have a significant impact on stock price movements. The paired sample t-test results show a significance value greater than 0.05, implying no significant difference in abnormal returns before and after the announcement. This finding supports the semi-strong form of the Efficient Market Hypothesis, suggesting that the market has efficiently absorbed public information regarding the dividend announcement. Therefore, it can be concluded that the dividend announcement did not trigger a significant reaction from investors in the Indonesian capital market.